RANCANGAN DAN SIMULASI MESIN PENCUCI JAHE MERAH - Thabitha Oktavia; Aldio Banurrohman; Dedy R Harahap; Juanda Juanda (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Red ginger plant has a latin name, namely Zingiber officinale rubrum variety which is one type of rhizome plant that is already popular for consumption as spices and medicinal ingredients. The process of washing red ginger is still done manually. So that the red ginger washing process becomes easier and does not take a long time, it is necessary to design a machine that can help the red ginger washing process. The design of the red ginger washing machine refers to the VDI 2222 design method which has 4 (four) stages, namely planning, conceptualizing, designing, and finishing. From this conceptualizing stage, 3 (three) variants of the design concept can be generated and assessed based on technical and economic aspects. The concept that has been selected is then optimized on several alternative functions and calculation analysis is carried out on the parts that are considered critical. Next, a explode simulation and assembly animation is made on the system using SolidWorks 2021 software to see an overview of the functional parts of the red ginger washing machine. This red ginger washing machine is equipped with 2 (two) revolving brushes made of nylon and also a water spraying system using pressurized water and in the washing compartment there is a door to make it easier to insert red ginger. This machine can clean as much as 25 kg of red ginger/washing process, making it easier to fill the red ginger into the hopper. Keywords: red ginger plant, washing machine, VDI 2222